Development of the construction of the cut-off blade from circular saws - Васильєв, Анатолій Володимирович; Попов, Станіслав Вячеславович; Даценко, Володимир Дмитрович (Technology audit and production reserves, 2015)
The aim of this article is to develop the design of the cut-off blade from circular saw, as a way of reducing consumption of cutting tool during cutting operations. The work is carried out in order to increase the reliability and service life of the cut-off blade of disk type, material of cutting parts are made of high speed steel P6M5. It is proposed the design of fixing of proposed cutter in the lathe tool carriers. The influence of the degree of sharpening the cutting edge on the firmness of cutting-off blade is offered. It is proposed to determine the severity of the blades by scanning on background of millimeter divisions by scanner with high resolution, allowing controlled rounded cutting edge with radius of 0,2 mm by diamond bar. Edge rounding allowed receiving increase sustainability of the tool to 1,8 times in a determined range of thickness of cut.